Simulating of human physiological supersystems: interactions of cardiovascular, thermoregulatory and respiratory systems - Grygoryan, R.D.; Degoda, A.G.; Lyudovyk, T.V.; Yurchak, O.I. (PROBLEMS IN PROGRAMMING, 2023)
Special quantitative model of the human thermoregulatory system (MTS) functioning with cardiovascular and lung systems is created. These systems form a human physiological supersystem (HPSS). MTS describes thermoregulatory responses to alterations of both external environmental physical characteristics and internal biological characteristics. Algorithms provide designing of scenarios including simulation of either short-time or long-time (hours or days) observations. Input data include different combinations of environmental variables (air or water temperature, air humidity, wind or water flow speed, light intensity, infrared radiation) for a naked or wear human, as well as for given dynamics of biological characteristics (rate of heat production including its components associated with metabolism and ATP molecules leasing during mental and physical activities). Human body is presented by a core, blood, and a skin compartments. Skin and lung evaporation are under hypothalamic control based on afferent impulse patterns from internal, and skin heat and cold receptors. Dynamic output data include blood, hypothalamic, and skin temperatures, hemodynamic parameters like heart rate, cardiac output, regional blood flows, vascular resistances, blood pressures, and regional blood volumes. Serotonin and melatonin concentrations modulating biological heat production rate are associated with a day/night light intensity. Currently, the PCbased simulator is autonomous software to be used both for educational purposes and for providing of special computer research. In a near future, this simulator has to be widened by models of kidneys, and a mechanism of liverpancreas interaction.Problems in programming 2023; 3: 81-90